Large-scale empirical study of electric vehicle usage patterns and charging infrastructure needs - Weipeng Zhan; Yuan Liao; Junjun Deng; Zhenpo Wang; Sonia Yeh (npj Sustainable Mobility and Transport)
Abstract As global electric vehicle (EV) adoption accelerates, granular analysis of empirical usage and charging patterns remains scarce. This study presents a unique large-scale empirical examination of 1.6 million EVs, including a broad array of vehicle types—private, taxi, rental, official, bus, and special purpose vehicle—across seven major Chinese cities with over 854 million observations of driving and charging events. Our findings illuminate significant heterogeneity in EV usage, battery energy, and charging behavior across vehicle types with notable city differences. Day-time high-power charging presents high loads on the electricity grid across all vehicle types, particularly from service-oriented vehicles, including taxis, rental cars, and buses. The maximum loads also are the highest in the center of the cities. Our study of large-scale EV usage offers critical insights for developing charging infrastructure, managing energy grids, and providing flexibility services, which are pivotal to the evolution of future transport ecosystems.